Reconstruction of Parotidectomy Defects. (2nd September 2014) - Peck, Jessica J.; Petrisor, Daniel; Cannady, Steven B.; Wax, Mark K.
Abstract : Objectives: Describe common cosmetic deformities and options for reconstruction following parotidectomy. Methods: The authors reconstructed parotid defects in 50 patients and will present an algorithm for reconstruction based on volume, location, and coexisting defects. Results: The parotid gland is the largest salivary gland in the head and neck, occupying a significant tissue volume. While not every parotidectomy requires reconstruction, excision of large parotid lesions, especially those involving the preauricular area, produce sizeable concavity and skeletonization of the mandible. The resulting cosmetic deformity can significantly affect patients' self‐image and negatively impact their quality of life. Free fat, alloderm, superficial musculoaponeurotic system, rotational sternocleidomastoid flap, and free tissue transfer are possible reconstructive options. Choosing an appropriate donor site requires consideration of the volume, location, and coexisting defects. Free fat grafts are best suited for small lateral parotid defects. In larger volume defects the amount of fat reabsorption is variable, making long‐term results less reliable. Similarly, the muscle atrophy of rotational sternocleidomastoid flaps limits their use to filling medium‐ sized defects, and the arch of rotation allows for only middle and inferior filling of the gland. Finally, large volume reconstruction of total parotidectomy defects, with or without skin, is best accomplished with free tissue transfer. Conclusions: Reconstructing parotid defects slightly increases operative time and blood loss, but patient satisfaction with the cosmetic outcome is high. Regardless of method used, same‐stage reconstruction of parotidectomy defects is advocated and of benefit to the patient. An algorithm for choosing one of several reconstructive options is presented.